Public Education in Preventing the Spread of Covid-19 - Rahmatya Nurmeidina (Borneo Community Development, 2021)
After one year has passed since Covid-19 has spread around the world, the spread of this virus is not over. Therefore, public education in preventing the spread of Covid-19 needs to be done. The method in community service activities is observation and interviews to determine the initial conditions of the local community, then the implementation of education in the form of direct counseling and installation of banners. This community service activity was carried out in Anjir Pasar Kota 1 Village, Pulau Telo Village and Candi Kelurahan. The result of this activity was the implementation of direct counseling in the form of providing information related to Covid-19 and how to prevent it by implementing health protocols, as well as installing banners regarding the application of health protocols. The installation of banners is carried out in strategic areas such as in markets. Apart from providing education and installing banners, this activity also distributed masks and hand sanitizers. The village head, village head, and local community responded well and enthusiastically to this community service activity.